2022
DOI: 10.48550/arxiv.2201.06535
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Yielding behavior of glasses under asymmetric cyclic deformation

Abstract: We consider the yielding behaviour of a model glass subjected to asymmetric cyclic shear deformation, wherein the applied strain varies between 0 and a maximum value γmax, and study its dependence on the degree of annealing of the glass and system size. The yielding behaviour of well annealed glasses (unlike poorly annealed glasses) display striking differences from the symmetric case, with the emergence of an intermediate strain regime with substantial plasticity but no yielding. The observed behaviour is sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
4
2
0
Order By: Relevance
“…It was further shown that rescaled distributions of nonaffine displacements during one cycle followed a power-law decay when the strain amplitude is below a critical value. In agreement with the recent results for athermal glasses under asymmetric cyclic shear [56], we found that the yielding transition in more stable glasses occurs at lower strain amplitudes. In the presence of thermal fluctuations, the yielding transition can be delayed for hundreds of shear cycles in a relatively large system when periodically deformed at strain amplitudes near a critical value.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It was further shown that rescaled distributions of nonaffine displacements during one cycle followed a power-law decay when the strain amplitude is below a critical value. In agreement with the recent results for athermal glasses under asymmetric cyclic shear [56], we found that the yielding transition in more stable glasses occurs at lower strain amplitudes. In the presence of thermal fluctuations, the yielding transition can be delayed for hundreds of shear cycles in a relatively large system when periodically deformed at strain amplitudes near a critical value.…”
Section: Discussionsupporting
confidence: 92%
“…3. These results are in agreement with a recent MD study on binary glasses under asymmetric cyclic deformation using athermal quasistatic shear protocol [56].…”
Section: Pk Jana and Nv Priezjevsupporting
confidence: 93%
See 2 more Smart Citations
“…These observations are consistent with findings in recent work by one of us on periodically sheared 3d atomistic glass formers 82 . There it was found that small samples that were moderately-or well-aged exhibit cyclic response at amplitudes well beyond the value of the strain at the stress peak.…”
Section: Sccsupporting
confidence: 93%